Setting The Upper Limit Of the Strong Rainbow Connection Number On the Jahangir Graph (3,m) By 2≤m≤3: Batas Atas Bilangan Strong Rainbow Connection Pada Graf Jahangir J(3,M) Dengan 2≤M≤3 - Dwi Novri Asmara (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
The Jahangir Graph J(n,m) for n ≥ 2, m ≥ 2 is a graph with the period of (nm + 1) that comprises a Cycle (Cn,m) by adding a close period to the period of m from Cn,m, having a graphn in Cn,m each other. A graph is called rainbow connection (rc) if every single line connecting two periods of u, v in G consists of rainbowu-vpath, and a graph is considered strong rainbow connection (src)if there is a line with the length of d(u,v), connecting two periods of u,v that consist of rainbow u-v geodesic. This research aimed to obtain upper limit srcin the Jahangir Graph of J(3, m)for m = 2 end m = 3. It was found that the upper limit of numeral src (J3,m) ≤ form = 2 and src J(3,m) ≤ for m = 3.